DESIGNING AN E-BOOKLET FOR MUSEUM NEGERI SUMATERA SELATAN TO ENDORSE PALEMBANG HISTORICAL TOURISM - Darmaliana; Yeny, Eli; Kholifah, Sulis (Politeknik Negeri Sriwijaya, 2022)
This inquiry was aimed at designing an e-booklet about Museum Negeri Sumatera Selatan to endorse Palembang’s historical tourism. The problem formulation in this research was formulated into a question: how to design the e-booklet of Museum Negeri Sumatera Selatan? The purpose of this study is to know the procedures to design an e-booklet for Museum Negeri Sumatera Selatan. The research and development method by Sukmadinata (2015) was applied to conduct the investigation. This method has three steps: a preliminary study, model development, and final product testing. Then the 7 stages (background research and investigation, concept, pitching, treatment, first draft, revision, and final draft) of script development by Friedmann (2014) are embedded into Sukmadinata’s idea. The draft design of the 38-page e-booklet of Museum Negeri Sumatera Selatan as historical tourism in Palembang was created based on the findings. Keyword: Research and Development, E-Booklet, Museum Negeri Sumatera Selatan